Prevalence, risk factors and molecular characterization of Cryptosporidium infection in cattle in Addis Ababa and its environs, Ethiopia - Manyazewal, Anberber; Stomeo, Francesca; Pal, Mahendra; Gezahegn, M.; Tesfaye, Mamo; Muthui, Lucy W.; Teklu, Wegayehu; Getachew, Tilahun (Elsevier, 2018)
A cross-sectional study was conducted to determine the prevalence and risk factors of Cryptosporidium infection and identify species of the parasite in cattle in central Ethiopia. Faecal samples, collected from 392 dairy cattle managed under intensive and extensive production system, were analyzed by the Modified Ziehl-Neelsen (MZN) microscopy, Nested PCR, PCR-RFLP and sequence analyses of the SSU rRNA gene of Cryptosporidium. The overall prevalence, the prevalence in the extensive and intensive farms was 18.6%, 11% and 21%, respectively. The infection was detected in 37.7% of the investigated farms with prevalence range of 7.4% -100%, and all of the six surveyed districts with significant (P = 0.000) prevalence difference. Restriction digestion and sequence analysis showed Cryptosporidium parvum and C. andersoni in 27% and 73% of the infections, respectively, showing an age related distribution pattern, C. parvum exclusively occurring in calves <2 months old and C. andersoni only in heifers and adult cattle. The infection was significantly associated with management system, farm location, herd size, source of drinking water, weaning age, presence of bedding, pen cleanness and cleanness of hindquarter. In conclusion, Cryptosporidium infection due to C. parvum and C. andersoni was prevalent in cattle in the study area. Cryptosporidium parvum has the concern of public health importance, especially to farm workers and people in close contact with cattle. Instigation of imperative control measure is suggested to lessen the risk of human infection and loss of production in dairy farms.